The Influence Of Customer Satisfaction, Product Quality And Promotion Strategy On Consumer Loyalty In The Study Of Consumers At PT Calista Beauty Clinic Medan - Hanny; Muhammad Agung Anggoro; Monika; Baby Angelia (Jurnal Mantik, 2021)
The research was conducted at PT Calista Beauty Clinic Medan. The research objective was to test and analyze the influence of Customer Satisfaction, Product Quality and Promotion Strategy on Study Consumer Loyalty at PT Calista Beauty Clinic Medan's Consumers. Consumer loyalty has decreased due to decreased customer satisfaction, product quality and less than optimal promotion strategies. The research method uses quantitative. The population in this study amounted to 198 consumers and the research sample amounted to 132 consumers. The sampling technique used was random sampling. Hypothesis testing partially and simultaneously Customer Satisfaction, Product Quality and Promotion Strategy had a positive and significant effect on Study Consumer Loyalty at PT Calista Beauty Clinic Medan's Consumers.